1995
DOI: 10.1212/wnl.45.7.1358
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI predicts outcome of temporal lobectomy

Abstract: We used actuarial methods to study outcome after temporal lobectomy in 135 consecutive patients classified into subgroups according to preoperative MRI findings. Sixty months after surgery, 69% of patients with foreign tissue lesions, 50% with hippocampal sclerosis, and 21% with normal MRIs had no postoperative seizures. An eventual seizure-free state of 2 years or more, whether the patient was seizure-free since surgery or not, was achieved by 80% of patients with foreign tissue lesions, 62% of those with hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

24
308
3
13

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(348 citation statements)
references
References 0 publications
24
308
3
13
Order By: Relevance
“…It was previously suggested that if there is hippocampal neuronal damage, it will cause ipsilateral fornix and mammilary body atrophy as a result of transneuronal degeneration 7 . Adjacent parahippocampal gyrus white matter (PHGWM) reduction 1,5,8,9 can be another associated finding (Figs 6 and 10) and is thought to be the cause of recurrent seizures after the first surgery (10-20%) 10 , as reported in previous studies. These patients were submitted to a new surgical intervention for extension of mesial ressected areas, with good results in most of the cases 11,12 .…”
supporting
confidence: 62%
“…It was previously suggested that if there is hippocampal neuronal damage, it will cause ipsilateral fornix and mammilary body atrophy as a result of transneuronal degeneration 7 . Adjacent parahippocampal gyrus white matter (PHGWM) reduction 1,5,8,9 can be another associated finding (Figs 6 and 10) and is thought to be the cause of recurrent seizures after the first surgery (10-20%) 10 , as reported in previous studies. These patients were submitted to a new surgical intervention for extension of mesial ressected areas, with good results in most of the cases 11,12 .…”
supporting
confidence: 62%
“…However, up to 40% of patients with mTLE and HS will continue to experience persistent postoperative seizures 9. There has therefore been an attempt in some studies to identify brain alterations, most typically increased atrophy from T1‐weighted MRI, in patients with continued seizures relative to those rendered seizure free.…”
mentioning
confidence: 99%
“…Consistent with a lack of consensus concerning the optimal anatomic target, the reported seizure-free outcomes are variable, although some etiologic associations seem to exist. Higher success rates appear to be achieved when mesial temporal sclerosis or focal lesions are present, whereas lower cure rates accompany normal preoperative brain imaging studies or unremarkable histopathology (3,8,9).…”
mentioning
confidence: 99%
“…Potential reasons for failures include nonfocal or bitemporal lobe epilepsy, unresected lesion, perilesional or postsurgical gliosis, extratemporal lesions, or diffuse cerebral disease, as may be present after meningitis or encephalitis (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation